The Effect of Brand Image and Brand Trust on Gojek Customer Loyalty in Yogyakarta Through Customer Satisfaction as an Intervening Variable - Effendi, Agsendo Muhammad; Sumadi (Business and Investment Review, 2023)
This study discusses the influence of brand image,brand trust, and user satisfaction on user loyalty Gojek in DI Yogyakarta. The measurement method uses multiple linear regression analysis to determine brand image,brand trust, and user satisfaction on user loyalty Gojek in DI Yogyakarta. The sample data was obtained from the questionnaire method. The sample used in this study was people of DI Yogyakarta who had filled out the questionnaires distributed. The number of questionnaires filled in and sampled were 95 respondend. Multiple regression results show that brand image, brand trust, and user satisfaction has a significant positive effect on user loyalty.